Negotiating Honor Through Indirectness: Off-Record Politeness Strategies in Sasak Elopement Rites - Lalu Nurul Yaqin (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
This study examines the off-record politeness strategies employed by the Pembayun Adat leaders during the Sasak elopement ceremony of the Sorong Serah ritual (Merariq). Using qualitative ethnography research. The study’s data were collected through participant observation, semi-structured interviews, and sixteen-hour audio-visual recordings of fifteen Sorong Serah ceremonies conducted in Lombok Timur, Indonesia. The data analysis employs Brown and Levinson’s (1987) politeness models, revealing four strategies: hinting, associative clues, overstating, and metaphorical. These strategies enable Pembayun to manage face-threatening acts (FTAs) used in critique, requests, and negotiations with minimal risk of confrontation. The results show that Pembayun politeness in this context is not merely a matter of linguistic preferences, but also a performance in cultural expectations of morality and ceremony. The study suggests a need to theorize a more culturally situated approach to politeness that captures the nexus between communication’s ethical and symbolic aspects in ritual contexts. By situating politeness in lived practices, this study contributes to cross-cultural pragmatics and ethnographic linguistics, providing relevant applications for intercultural communication, ritual language analysis, and culturally responsive dialogue strategies. It advances politeness theory by emphasizing the need for culturally specific models that account for moral symbolism, high-context communication, and collectivist norms.